Pengaruh Ukuran Perusahaan, Risiko Likuiditas dan Risiko Kredit Terhadap Kinerja Keuangan pada PT BPR Tangerang - Mahmuri, Gatot; Taufiqurrochman, Cecep (Riviera Publishing, 2026)
Financial performance is a key indicator in assessing the operational success of Rural Banks (BPR). As financial intermediary institutions, BPRs must effectively manage their assets and various risks to maintain profitability and financial stability. Factors such as firm size, liquidity risk, and credit risk play important roles in determining the financial performance of banks. This research aims to analyze the influence of firm size, liquidity risk, and credit risk on the financial performance of PT BPR Tangerang. This research uses a quantitative approach with secondary data obtained from the financial statements of PT BPR Tangerang for the period 2020–2024. The data were analyzed using regression analysis to examine the effect of each independent variable on financial performance. The results show that firm size, measured by total assets, has a positive and significant effect on financial performance. Liquidity risk, measured by the cash ratio, also has a positive and significant effect, indicating that adequate liquidity enables banks to meet short-term obligations without disrupting the management of productive assets. In contrast, credit risk, measured by Non-Performing Loans (NPL), has a negative and significant effect on financial performance, as higher levels of problematic loans reduce bank profitability. Simultaneously, firm size, liquidity risk, and credit risk significantly influence the financial performance of PT BPR Tangerang. Therefore, optimal asset management and effective management of liquidity and credit risk are essential to improve profitability and maintain the financial stability of the bank.